Polyvinyl alcohol-based organic conductive gel as well as preparation method and application thereof

By introducing organic conductive gels with PVA-ANF-conductive particles into traditional smart hydrogels, and preparing them by freeze-thawing method, the problems of poor mechanical properties and slow response speed of traditional hydrogels are solved, and higher mechanical properties and conductive properties are achieved, and suitable for smart materials and flexible electronic devices.

CN119899398AInactive Publication Date: 2025-04-29FUJIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510075442.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional intelligent hydrogel strain sensors have problems such as poor mechanical properties, slow response speed, toxicity, poor circulation stability and low environmental stability.

Method used

By introducing organic conductive gel preparation method of polyvinyl alcohol (PVA)-aramid nanofiber (ANF)-conductive particles, hydrogels are prepared by freeze-thawing method to improve their mechanical properties, conductivity and thermal stability.

Benefits of technology

It significantly improves the mechanical and conductive properties of the hydrogel, improves its application potential in smart materials and flexible electronic devices, and has a greener preparation process, faster response speed, and has stronger water locking performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899398A_ABST
    Figure CN119899398A_ABST
Patent Text Reader

Abstract

The invention provides polyvinyl alcohol-based organic conductive gel as well as a preparation method and application thereof, and belongs to the technical field of hydrogel. The preparation method comprises the following steps: mixing polyvinyl alcohol powder with high-concentration aramid nanofiber (ANF) dispersion liquid in different proportions to obtain a PVA-ANF organic gel system; adding conductive particles with different proportions into the PVA-ANF organic gel system, and uniformly dispersing to obtain a PVA-ANF-conductive particle mixed solution; the PVA-ANF-conductive particle mixed solution is subjected to a freeze thawing method, and the organic conductive gel is prepared. By introducing mechanical and electrical reinforcing materials such as the ANF and the conductive particles, the mechanical property and the electrical property of the hydrogel can be effectively improved. The ANF and the conductive particles not only increase the strength and durability of the gel, but also endow the gel with conductivity and good thermal stability, so that the application potential of the gel in the fields of flexible electronic devices and the like is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogels, and in particular to a method for preparing a polyvinyl alcohol (PVA)-aramid nanofiber-conductive particle (PVA-ANF-conductive particle) organic conductive gel based on polyvinyl alcohol (PVA), as well as a PVA-ANF-conductive particle organic conductive gel based on PVA prepared by the preparation method and the application of the PVA-ANF-conductive particle organic conductive gel based on PVA in flexible electronic devices. Background Art

[0002] The unsatisfactory mechanical properties of traditional smart hydrogel strain sensors are a prominent problem facing their application. A strain sensor is a device that can detect the deformation of an object through a signal (usually an electrical signal). The preparation of strain sensors requires stretchable materials with a stretchability of more than 300%, rather than rigid materials. One of the key prerequisites for strain sensors to monitor a large range of movements of human limbs is the ability to withstand high and reversible tensile deformations. Compared with textiles or traditional elastic substrates, hydrogels are more promising candidate materials for the preparation of strain sensors because they can undergo a larger range of deformations and are more similar to human skin due to their flexibility and biocompatibility.

[0003] Traditional smart hydrogel strain sensors are usually prepared by the following method:

[0004] Methods for preparing gel: chemical cross-linking method, radiation cross-linking method, solvent evaporation method, pH / temperature response method, self-assembly method, and electrochemical cross-linking method.

[0005] (1) Preparation of gel using freeze-thaw method: As a physical cross-linking method for gel formation, freeze-thaw method has been widely used in materials science, especially in the preparation of hydrogels. It was first used for PVA hydrogel. Through alternating freezing and thawing treatments, hydrogen bonds or crystal regions are formed between molecular chains. It has gradually been applied to other polymer materials such as polyacrylamide and natural polysaccharides. In recent years, the microstructure of gel has been optimized by regulating freeze-thaw cycle parameters, and its mechanical properties and swelling characteristics have been improved to meet various needs such as drug delivery and tissue engineering. Future development trends include green environmental protection and sustainable preparation, emphasizing the reduction of energy consumption; combining with other physical or chemical cross-linking methods to achieve multifunctionality; integrating with nanomaterials and biomaterials to improve the mechanical strength and biocompatibility of gels; and the development of cryogenic technology, in order to prepare gels at higher temperatures and expand their application scenarios. Due to its advantages such as greenness and low toxicity, freeze-thaw method has broad application prospects in the field of multifunctional smart materials.

[0006] (3) Borax chemical cross-linking method: Compared with the freeze-thaw method, the main disadvantages of the borax chemical cross-linking method include poor biocompatibility, chemical residue problems, and unstable mechanical properties. Borax cross-linking usually leaves chemical reagent residues that are difficult to completely remove, which poses potential risks to the environment and biological systems, limiting its application in medical and biomaterials. In addition, the gel structure formed by borax cross-linking is weak, with poor mechanical strength and durability, and it is difficult to meet the requirements of applications with high mechanical properties. The freeze-thaw method has stronger mechanical properties and responsiveness due to its stable physical cross-linking network. At the same time, borax chemical cross-linking has low responsiveness to environmental stimuli, making it difficult to achieve intelligent regulation, and has high energy consumption under certain temperature and solvent conditions. In comparison, the freeze-thaw method is simpler and more environmentally friendly in preparation, so it has more advantages in biosafety, mechanical properties and smart material applications.

[0007] In summary, the existing intelligent hydrogel strain sensors have the following defects:

[0008] First, in the traditional chemical cross-linking method, borax is toxic and harmful to the human nervous system, liver and kidney function, and has reproductive toxicity to pregnant women and children, which may lead to decreased fertility or developmental problems. In addition, borax residues will pollute the environment, irritate the skin and mucous membranes, and long-term contact may cause allergic or inflammatory reactions. Therefore, the amount of borax used must be strictly controlled and fully cleaned during application to reduce its harm.

[0009] Secondly, in addition to poor mechanical properties, traditional smart hydrogels also have problems such as slow response speed, poor cycle stability and low environmental stability. For example, they are easy to lose water or degrade in high temperature, dry or organic solvent environments, which limits their service life. In addition, the functions are usually relatively single and it is difficult to meet multi-functional requirements. For example, materials with high mechanical strength, conductivity and self-healing ability are rare. At the same time, the preparation process of some hydrogels is relatively complicated and requires specific conditions such as low temperature or oxygen-free environment, which increases the difficulty and cost of production and is not conducive to large-scale application. Summary of the invention

[0010] In view of this, in order to solve the technical problems that traditional smart hydrogels have poor mechanical properties, slow response speed, toxicity, poor cycle stability and low environmental stability, on the one hand, the present invention provides a method for preparing a PVA-ANF-conductive particle organic conductive gel based on PVA, which can effectively improve the mechanical properties of the hydrogel and enhance its tensile strength and fracture toughness by introducing mechanical and electrical performance enhancing materials such as ANF and conductive particles. ANF and conductive particles not only increase the strength and durability of the gel, but also give it conductivity and good thermal stability, greatly improving its application potential in the fields of smart materials, flexible electronic devices, etc. The hydrogel prepared by the freeze-thaw method has been significantly improved in performance and application prospects. Its preparation method is greener, has a faster response speed, better water-locking performance, and has stronger mechanical properties and conductive properties.

[0011] To achieve the above object, the present invention provides the following technical solutions:

[0012] The preparation method of PVA-ANF-conductive particle organic conductive gel based on PVA comprises the following steps:

[0013] Step i, mixing PVA powder with high-concentration ANF dispersion in different proportions to obtain a PVA-ANF mixed solution;

[0014] Step ii, adding conductive particles in different proportions to the PVA-ANF organogel system obtained in step i, dispersing the conductive particles uniformly, and obtaining a PVA-ANF-conductive particle mixed solution;

[0015] Step iii: using the freeze-thaw method to prepare an organic conductive gel using the PVA-ANF-conductive particle mixed solution in step ii.

[0016] Preferably, in step i, the mass percentage of ANF in the PVA-ANF mixed solution is 1% to 5%.

[0017] Preferably, in step i, the mass percentage of ANF in the PVA-ANF mixed solution is 2%.

[0018] Preferably, in step ii, the conductive particles are one of soluble electrolyte salts, carbon nanotubes, graphene and its derivatives, conductive MOFs, MXenes and MBenes.

[0019] Preferably, in step ii, the mass percentage of the conductive particles in the PVA-ANF-conductive particles mixed solution is 0.1% to 10%.

[0020] Preferably, a stably dispersed high-concentration ANF solution was prepared by a proton donor-assisted deprotonation method.

[0021] Preferably, in step i, the preparation method of PVA gel is as follows:

[0022] PVA powder was added to dimethyl sulfoxide and heated in a water bath to dissolve it.

[0023] In a second aspect, the present invention provides a PVA-ANF-conductive particle organic conductive gel based on PVA, which is prepared according to the above-mentioned method for preparing the PVA-ANF-conductive particle organic conductive gel based on PVA.

[0024] In a third aspect, the present invention also provides the use of the above-mentioned PVA-ANF-conductive particle organic conductive gel based on PVA in flexible electronic devices.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The preparation method of the PVA-ANF-conductive particle organic conductive gel based on PVA provided by the present invention can effectively improve the mechanical properties (stretchability and fracture toughness) and electrical properties (conductivity) of the hydrogel by introducing reinforcing materials such as ANF and conductive particles. ANF and conductive particles not only increase the strength and durability of the gel, but also give it electrical conductivity and good thermal stability, greatly improving its application potential in the fields of smart materials, flexible electronic devices, etc. The hydrogel prepared by the freeze-thaw method has been significantly improved in performance and application prospects. Its preparation method is greener, has a faster response speed, better water-locking performance, and has stronger mechanical properties and conductive properties.

[0027] Compared with the traditional chemical cross-linking method, the freeze-thaw method has significant advantages as a physical cross-linking method. It does not require the use of toxic chemical reagents, avoids the toxicity, environmental pollution and irritation to the skin and mucous membranes that borax may bring, and has better biocompatibility. The freeze-thaw method also has high environmental stability and response speed, can respond quickly to changes in temperature and pH, and its preparation process is relatively simple, reducing production difficulty and cost.

[0028] Since the dispersibility of ANF in proton-rich systems is poor, the present invention uses PVA as a "bridge" to improve the dispersibility of ANF in the hydrogel matrix. Due to the strong interaction between ANF and the matrix, stress can be effectively transferred from the matrix to ANF, thereby improving the tensile strength and elongation at break of the hydrogel.

[0029] The hydrogel prepared by the present invention has a multi-crosslinked network in structure, in which PVA and ANF provide a solid support framework, while the conductive particles give the material good conductivity. Thanks to these characteristics, the PVA-ANF-conductive particle organic conductive gel can be applied to multiple fields, such as flexible electronic devices. Due to its conductivity and flexibility, it is suitable for sensors, flexible electrodes, etc. of flexible electronic devices.

[0030] In summary, the present invention achieves the goal of improving the multifunctionality, environmental adaptability and stability of the hydrogel while ensuring its high mechanical strength, and the preparation process is simple and environmentally friendly, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of PVA-ANF-conductive particle organic conductive gel.

[0032] Figure 2 The figure is a mechanical property diagram of toughened PVA-ANF organogel; wherein, PVA:ANF=99:1 is a high concentration of ANF with a 1% addition ratio, PVA:ANF=98:2 is a high concentration of ANF with a 2% addition ratio, PVA:ANF=97:3 is a high concentration of ANF with a 3% addition ratio, PVA:ANF=96:4 is a high concentration of ANF with a 4% addition ratio, and PVA:ANF=95:5 is a high concentration of ANF with a 5% addition ratio;

[0033] Figure 3 The mechanical properties of toughened PVA-ANF-NaCl organic conductive gel; 0M, 0.1M, 0.5M, 1M and 2M represent NaCl concentrations of 0%, 0.1%, 0.5%, 1% and 2%, respectively;

[0034] Figure 4 It is a mechanical property diagram of PVA-ANF-CNT organic conductive gel; wherein, PVA:ANF:CNT=98:2:1 is a high concentration of ANF with a 2% addition ratio, and the mass percentage of CNT (carbon nanotube) and PVA-ANF is 1%; PVA:ANF:CNT=98:2:2 is a high concentration of ANF with a 2% addition ratio, and the mass percentage of CNT (carbon nanotube) and PVA-ANF is 2%; PVA:ANF:CNT=98:2:3 is a high concentration of ANF with a 2% addition ratio, and the mass percentage of CNT (carbon nanotube) and PVA-ANF is 3%; PVA:ANF:CNT=98:2:5 is a high concentration of ANF with a 2% addition ratio, and the mass percentage of CNT (carbon nanotube) and PVA-ANF is 5%; PVA:ANF:CNT=98:2:10 is a high concentration of ANF with a 2% addition ratio, and the mass percentage of CNT (carbon nanotube) and PVA-ANF is 10%;

[0035] Figure 5It is a mechanical property diagram of PVA-ANF-MXene organic conductive gel; Among them, PVA:ANF:MXene=98:2:0 is a high concentration of ANF with a 2% addition ratio, and the mass percentage of MXene and PVA-ANF is 0%; PVA:ANF:MXene=98:2:0.1 is a high concentration of ANF with a 2% addition ratio, and the mass percentage of MXene and PVA-ANF is 0.1%; PVA:ANF:MXene=98:2:0.3 is a high concentration of ANF with a 2% addition ratio, and the mass percentage of MXene and PVA-ANF is 0.3%; PVA:ANF:MXene =98:2:0.5 means the addition ratio of high concentration ANF is 2%, and the mass percentage of MXene and PVA-ANF is 0.5%; PVA:ANF:MXene=98:2:1 means the addition ratio of high concentration ANF is 2%, and the mass percentage of MXene and PVA-ANF is 1%; PVA:ANF:MXene=98:2:5 means the addition ratio of high concentration ANF is 2%, and the mass percentage of MXene and PVA-ANF is 5%; PVA:ANF:MXene=98:2:10 means the addition ratio of high concentration ANF is 2%, and the mass percentage of MXene and PVA-ANF is 10%. DETAILED DESCRIPTION

[0036] Terminology explanation:

[0037] ANF ​​(aramid nanofiber): ANF has extremely strong strength and modulus, is lightweight and corrosion resistant, and therefore has great potential for application in many fields, such as reinforcing composite materials, flexible electronic devices, filter materials, functional films in energy storage devices, and protective materials. In addition, ANF can form a high-viscosity colloidal solution in a solvent.

[0038] PVA: PVA refers to polyvinyl alcohol (Polyvinyl Alcohol), which is a water-soluble synthetic polymer with good film-forming properties, adhesion, flexibility and chemical stability. PVA is commonly used in coatings, adhesives, textiles, papermaking, building materials, and packaging materials in the food and pharmaceutical fields. After dissolving in water, PVA can form a stable colloidal solution, which is suitable for the preparation of films or fibers. Due to its excellent biocompatibility and degradability, PVA is also used in biomedical materials such as wound dressings, drug release carriers and tissue engineering scaffolds. In addition, PVA can improve the mechanical properties and thermal stability of the material after being compounded with other materials, so it is widely used in the research and development of functional materials.

[0039] Conductive particles: can be soluble electrolyte salts such as sodium chloride, carbon nanotubes, graphene and its derivatives, conductive MOF, MXenes, MBenes, etc.

[0040] PVA-ANF-conductive particle organic conductive gel: The introduction of conductive particles gives the organic gel conductivity, and can further improve the mechanical properties, electrical properties and multifunctionality of the hydrogel through interaction with PVA and ANF.

[0041] The present invention provides a method for preparing a PVA-ANF-conductive particle organic conductive gel based on PVA, comprising the following steps:

[0042] Step (1), PVA powder is mixed with high concentration ANF in different proportions, preferably heated to 80° in a water bath, mechanically stirred (1200 rpm) for 2 hours, and a viscous light yellow liquid is formed after stirring to obtain a PVA-ANF mixed solution. Wherein, the preparation of the above mixed solution requires the use of PVA powder and DMSO as solvents. The preparation method can be selected from the following preparation methods:

[0043] Prepare the materials: Make sure you have exactly 10g of PVA powder and 90g of DMSO. In addition, you will need a water bath, magnetic stirrer, and container to dissolve the mixture.

[0044] Add DMSO in batches: PVA powder is placed in a container, and then DMSO is added to the PVA powder in 5 batches, 2 g each time.

[0045] Heating and stirring: Heat the mixture to 90°C in a water bath and ensure that the magnetic stirrer is running at a high speed to completely dissolve the PVA powder.

[0046] Dissolution process: PVA powder will gradually dissolve in DMSO under heating and rapid stirring. This process may take some time, and make sure the temperature of the mixture remains at 90°C.

[0047] Stir until homogeneous: As DMSO is added and stirred, the mixture will gradually become homogeneous. Pay attention to the state of the mixture to ensure that the PVA powder is completely dissolved.

[0048] Preparation is complete: When all the DMSO is added and the PVA powder is completely dissolved, a uniform DMSO dispersion of PVA will be obtained.

[0049] High-concentration ANF is prepared by proton donor-assisted deprotonation to prepare stably dispersed high-concentration ANF. Ensure the uniform distribution of ANF in the PVA matrix to avoid agglomeration, thereby improving the mechanical properties and thermal stability of the hydrogel on a macro scale. This dispersion technology is a composite hydrogel that forms a uniform network structure. The preparation method can be selected as follows:

[0050] Prepare materials: 2 g polyterephthalamide (PPTA) fiber, 3 g potassium hydroxide (KOH) as a proton donor, 100 mL DMSO and an appropriate amount of deionized water.

[0051] Mixing: Mix the PPTA fiber with KOH, DMSO and deionized water.

[0052] Mechanical stirring: The mixture was placed in a sealed environment for mechanical stirring at room temperature to ensure that all components were fully in contact and reacted. The stirring time lasted for 4 hours.

[0053] Observe the reaction: During the stirring process, the mixture was observed to gradually turn dark black, which is a sign of the occurrence of deprotonation reaction.

[0054] Obtaining ANF solution: After deprotonation reaction, a stably dispersed high-concentration ANF solution can be obtained.

[0055] The key to this method is to use a proton donor (e.g., KOH) to assist the deprotonation process of PPTA fibers to obtain a highly dispersed ANF solution. This process affects the physical properties of ANF, such as improving its conductivity or changing its morphological structure.

[0056] Step (2), adding conductive particles in different proportions (mass percentage of the PVA-ANF organogel system) to the PVA-ANF mixed solution obtained in step (1), dispersing them evenly, and obtaining a PVA-ANF-conductive particle mixed solution.

[0057] Step (3), the PVA-ANF-conductive particle mixed solution in step (2) is subjected to freeze-thaw method to prepare an organic conductive gel. The PVA matrix is ​​cross-linked with the network structure of ANF and conductive particles by freeze-thaw physical cross-linking method (freeze-thaw method) to achieve multi-level structural enhancement of the composite hydrogel. This mechanism significantly improves the fracture toughness, tensile properties and electrical properties of the composite material, while giving it environmental stability.

[0058] In the present invention, in step (1), the mass percentage of ANF in the PVA-ANF mixed solution is 1% to 5%.

[0059] In the present invention, in step (1), the mass percentage of ANF in the PVA-ANF mixed solution is 2%.

[0060] In the present invention, in step (2), the mass percentage of the conductive particles in the PVA-ANF-conductive particles mixed solution is 0.1% to 10%.

[0061] In the present invention, in step (1), the preparation method of PVA gel is as follows:

[0062] PVA powder was added to DMSO and heated in a water bath to dissolve it.

[0063] In a second aspect, the present invention provides a PVA-ANF-conductive particle organic conductive gel based on PVA, which is prepared according to the above-mentioned method for preparing the PVA-ANF-conductive particle organic conductive gel based on PVA.

[0064] In a third aspect, the present invention also provides the application of the above-mentioned PVA-ANF-conductive particle organic conductive gel based on PVA in flexible electronic devices, such as flexible sensors, etc.

[0065] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0066] Example 1

[0067] Preparation of PVA-ANF organogel

[0068] Step (1), take 10 g of PVA powder and 90 g of DMSO, and add the PVA powder to DMSO in 5 batches, 2 g each time.

[0069] Step (2), dissolving the mixed solution in a water bath at 90° C., with the magnetic stirring speed at 1200 rpm, so that the PVA is dissolved more fully.

[0070] Step (3), preparing a DMSO dispersion of ANF by a proton donor-assisted deprotonation method: 2 g of PPTA fiber, 3 g of KOH, 100 mL of DMSO and 4 mL of deionized water were mixed, and mechanically stirred in a sealed environment at room temperature for 4 hours, and allowed to react until dark black, thereby obtaining a DMSO dispersion of ANF.

[0071] Step (4), take a certain amount of ANF DMSO dispersion and PVA DMSO dispersion and mix them, heat in a water bath at 80°C, mechanically stir at a speed of 1200rpm, and stir for 2 hours. After stirring, a viscous light yellow liquid is formed, which is the PVA-ANF mixed solution. Among them, the mass proportion of ANF (mass percentage of the PVA-ANF mixed solution) is 1%, 2%, 3%, 4%, and 5%.

[0072] Step (5), pour the uniformly mixed mixture into a mold and freeze-thaw for 10 hours, and thaw for one hour. This cycle is repeated three times. After three freeze-thaw cycles, the PVA-ANF organogel removed from the mold is placed in an exchange solution for exchange. The exchange time is 24 hours to obtain a mixed toughened PVA-ANF organogel. The exchange solution is a mixture of DMSO and deionized water, and the volume proportion of DMSO is 25%.

[0073] Step (6), the toughened PVA-ANF organogel is subjected to mechanical property testing, and the test results are as follows: Figure 1 As shown in the figure, it can be seen that when the mass proportion of ANF is 2%, the mechanical properties of the toughened PVA-ANF organogel are the best. Specific properties: fracture strain 520%, maximum stress 1984KPa, Young's modulus 360KPa, fracture toughness 5.2MJ m -3 .

[0074] from Figure 1 It can be seen that the toughness and fracture strain of ANF with a proportion of 2% are the best. Therefore, the following experiments use PVA-ANF 2% as the experimental substrate for the following Examples 2-4.

[0075] Example 2

[0076] Preparation of PVA-ANF-NaCl organic conductive gel

[0077] Steps (1) to (4) are the same as those in Example 1, wherein the mass percentage of ANF obtained in step (4) (mass percentage of PVA-ANF organogel) is 2%.

[0078] Step (5), pour the mixed solution into a mold and freeze-thaw for 10 hours, and thaw for one hour. This cycle is repeated three times. After three freeze-thaw cycles, the PVA-ANF organic gel removed from the mold is placed in an exchange solution for exchange. The exchange time is 24 hours to obtain a toughened PVA-ANF-NaCl organic conductive gel. The exchange solution is a mixture of DMSO, sodium chloride and deionized water, the mass ratio of DMSO to deionized water is 1:2, and the concentration of NaCl is 0M, 0.1M, 0.5M, 1M, 2M.

[0079] Step (6), the PVA-ANF-NaCl conductive organic hydrogel is subjected to a mechanical property test, and the test results are as follows: Figure 2 As shown in the figure, it can be seen that when the NaCl concentration is 0.5 M, the mechanical properties of the PVA-ANF-NaCl organic conductive gel are the best. Specific properties, fracture strain 454%, maximum stress 2493 KPa, Young's modulus 530 KPa, fracture toughness 6.06 MJ m -3 .

[0080] Example 3

[0081] Preparation of PVA-ANF-CNT organic conductive gel

[0082] Steps (1) to (4) are the same as in Example 2

[0083] Step (5), mixing the PVA-ANF mixed solution with carbon nanotubes, wherein the mass ratio of carbon nanotubes to PVA-ANF is 1:100, 2:100, 3:100, 4:100, 5:100, and 10:100. The mixing method is mechanical stirring, the rotation speed is 1800rpm, and the water bath temperature is 80°C. Pour the evenly mixed mixed solution into a mold for 10 hours of freeze-thaw and thaw in one hour. This cycle is repeated three times. After three freeze-thaw cycles, the PVA-ANF-CNT organic conductive gel removed from the mold is placed in an exchange solution for exchange to obtain a mixed toughened PVA-ANF-CNT organic conductive gel. Among them, the exchange solution is a mixture of DMSO and deionized water, and the volume proportion of DMSO is 25%.

[0084] Step (6), the mechanical properties of the PVA-ANF-CNT organic conductive gel are tested. The test results are as follows: Figure 3 As shown. It can be seen that when the CNT content is 10%, the mechanical properties of PVA-ANF-CNT organic conductive gel are the best. Specific properties, fracture strain 412%, maximum stress 1418KPa, Young's modulus 306KPa, fracture toughness 3.1MJ m -3 .

[0085] Example 4

[0086] Preparation of PVA-ANF-MXene organic conductive gel

[0087] Steps (1) to (4) are the same as in Example 2

[0088] Step (5), usually, hydrochloric acid (9M, 40mL), lithium fluoride (2g) and Ti3AlC2 powder (2g) are first added to a polytetrafluoroethylene beaker under stirring. Next, the mixture is stirred at 80°C for 72 hours. Thereafter, the resulting mixture is repeatedly washed with deionized water until its pH value reaches 7. Subsequently, DMSO is added to the mixture and ultrasonically treated for 1 hour. The mixture is centrifuged (10000rpm, 10min) to collect the precipitate. The above precipitate is freeze-dried for three days to form a solid, and then the solid is ground to obtain MXene powder. Take 1.5g of MXene powder and dissolve it in 30mL of DMSO to form a 50mg / ml DMSO dispersion of MXene. The specific dissolution method is to grind the solid MXene, add the DMSO solution after grinding, and stir magnetically at room temperature for 18 hours, and the magnetic stirring speed is 1200rpm, so as to obtain a DMSO dispersion of MXene.

[0089] Step (6), mix the PVA-ANF mixed solution with the DMSO dispersion of MXene, wherein the mass ratio of MXene to PVA-ANF is 0.1:100, 0.3:100, 0.5:100, 1:100, 5:100, and 10:100. The mixing method is mechanical stirring, the rotation speed is 1800rpm, and the water bath temperature is 80°C. Pour the evenly mixed mixed solution into the mold for 10 hours of freeze-thaw and thaw in one hour. This cycle is repeated three times. After three freeze-thaw cycles, the PVA-ANF-MXene organic conductive gel removed from the mold is placed in the exchange liquid for exchange to obtain a mixed toughened PVA-ANF-MXene organic conductive gel. Among them, the exchange liquid is a mixture of DMSO and deionized water, and the volume proportion of DMSO is 25%.

[0090] Step (7), testing the mechanical properties of the PVA-ANF-MXene organic conductive gel, such as Figure 4 As shown. It can be seen that when the MXene content is 0.5%, the mechanical properties of PVA-ANF-MXene organic conductive gel are the best. Specific properties, fracture strain 676%, maximum stress 2931KPa, Young's modulus 432KPa, fracture toughness 9.04MJ m -3 .

Claims

1. A method for preparing a PVA-ANF-conductive particle organic conductive gel based on PVA, characterized in that: The steps include: Step i, mixing PVA powder with high-concentration ANF dispersion in different proportions to obtain a PVA-ANF mixed solution; Step ii, adding conductive particles in different proportions to the PVA-ANF organogel system obtained in step i, dispersing the conductive particles uniformly, and obtaining a PVA-ANF-conductive particle mixed solution; Step iii: using the freeze-thaw method to prepare an organic conductive gel using the PVA-ANF-conductive particle mixed solution in step ii.

2. The method for preparing the PVA-ANF-conductive particle organic conductive gel based on PVA according to claim 1, characterized in that: In step i, the mass percentage of ANF in the PVA-ANF mixed solution is 1% to 5%.

3. The method for preparing the PVA-ANF-conductive particle organic conductive gel based on PVA according to claim 1, characterized in that: In step i, the mass percentage of ANF in the PVA-ANF mixed solution is 2%.

4. The method for preparing the PVA-ANF-conductive particle organic conductive gel based on PVA according to claim 1, characterized in that: In step ii, the conductive particles are one of soluble electrolyte salts, carbon nanotubes, graphene and its derivatives, conductive MOFs, MXenes and MBenes.

5. The method for preparing the PVA-ANF-conductive particle organic conductive gel based on PVA according to claim 1, characterized in that: In step ii, the mass percentage of the conductive particles in the PVA-ANF-conductive particles mixed solution is 0.1% to 10%.

6. The method for preparing the PVA-ANF-conductive particle organic conductive gel based on PVA according to claim 1, characterized in that: Stably dispersed high-concentration ANF solutions were prepared by a proton donor-assisted deprotonation method.

7. The method for preparing a PVA-ANF-conductive particle organic conductive gel based on PVA according to any one of claims 1 to 6, characterized in that: In step i, the preparation method of PVA gel is as follows: PVA powder was added to dimethyl sulfoxide and heated in a water bath to dissolve it.

8. PVA-ANF-conductive particle organic conductive gel based on PVA, characterized in that: The organic conductive gel is prepared according to the method for preparing the PVA-ANF-conductive particle organic conductive gel based on PVA according to any one of claims 1 to 7.

9. Application of the PVA-ANF-conductive particle organic conductive gel based on PVA as claimed in claim 8 in flexible electronic devices.